On the nature of a large anticlinal fold in the Upper Kama salt deposit, its geomechanical and gas-geochemical zonality - I.I. Chaikovskiy; O.V. Ivanov; I.L. Pan’kov; E.P. Chirkova (Учёные записки Казанского университета: Серия Естественные науки)
Large (more than 10 m in height) folds complicate the longwall mining of potash salts and are accompanied with the formation of foci of gas-dynamic phenomena. In this study, to identify the folding nature, changes in the physical properties of its rocks, and the distribution of gases, we analyzed the structural plan of the mined formation, performed structural geological observations, determined the amount and composition of associated gases, and identified the deformation parameters of salts. It was found that a separate flexure-like fold with a height of more than 30 m developed at the intersection of two fold systems of the salt stratum. During the formation of this dislocation, the sylvinite layer underwent folding catagenesis, which led to the boudinage and the appearance of a directive texture, the intensity of which decreases with the distance from the fold. In terms of the geomechanics, the following two zones were formed: near, slightly weakened rocks with subzones of stiffer (about 0 m) and more plastic (about 58 m) rocks, as well as distant, heavily weakened rocks with subzones of more viscous and less elastic (about 131 m) rocks and less viscous and more elastic (about 241 m) rocks. Their formation, along with the flattening of grains, can be associated with the squeezing and spatial redistribution of gas-liquid inclusions. In the process of gas-phase diffusion, zonality in the distribution of gases was observed (methane and its homologues → nitrogen → carbon dioxide). It turned out to be consistent with their migration ability. The high value of the C2H6/i-C4H10 index suggests that a part of the hydrocarbon gases could have been generated in situ from the organic matter of salts during the fold catagenesis. It was established that the zone of influence of a 30-m fold is 380–500 m, which makes it possible to predict the formation of free gases foci in this interval and the adoption of appropriate protection measures.